TINGKAT PENGETAHUAN DAN SIKAP PEDAGANG MAKANAN JAJANAN PASAR TERHADAP PENGGUNAAN PEWARNA YANG DILARANG DI PASAR-PASAR KOTA SEMARANG - Rila Dini Ayu Larasati; Yuwono Setiadi; Dyah Nur Subandriani; Arintina Rahayuni; Ana Yuliah Rahmawati (Poltekkes Kemenkes Semarang, 2018)
Background : The use of banned dyes In making foodin general to give a striking color to food so that it can attract consumers to buy, but the trader was not aware of the dangers of using banned dyes.This is because the level of knowledge and attitudes of food traders are less related to the use offood coloring agents. Objective : Knowing the relationship between the level of knowledge and the attitude of market food vendors to the use of dyes that are prohibited in the Semarang city market. Method : This research is a descriptive analytic study with cross sectional design. Sampling uses cluster techniques to 8 market samples.The collected data are knowledge and attitude data with questionnaire and interview measurement tools.Data on the use of dyesusing the phenylhydrazine method. Results : Traders have knowledge in good categories (87,5%)while traders have the same attitude comparison between those who support and not support (50%)and the results of laboratory tests conducted by the university on August 17 showed negative results on the use of banned dyes but there were 2 markets using dyes that were not prohibited, namelyEritrosin. Conclusion : All traders do not use dyes that are banned in cenil and putu mayang